Comparison of the mental symptoms in peritoneal dialysis and haemodialysis patients - (:unkn) unknown (A. CARBONE Editore, 2015)
Introduction: Although dialysis has become a life-prolonging therapy for patients with end-stage renal disease, dialysis patients deal with serious problems. Dialysis patients face major mental problems such as depression, anxiety and stress and paranoia. The aim of this study was to evaluate and compare mental symptoms in chronic haemodialysis and peritoneal dialysis patients. Materials and methods: One hundred twenty-nine haemodialysis and 100 peritoneal dialysis patients were included in this study. The Brief Symptom Inventory (BSI) was used for the mental symptoms evaluation. Statistical analysis was performed using chisquare, t-test and Pearson's correlation analysis. Results: Although the BSI and its subscales such as the mean global severity index, somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety and paranoid ideation scores of the haemodialysis and peritoneal dialysis patients were similar, hostility, phobic anxiety and psychosis scores were significantly higher in the peritoneal dialysis patients than in haemodialysis patients. The BSI subscales such as anxiety, hostility and psychosis were negatively correlated with age in the haemodialysis patients, and hostility was negatively correlated with age in the peritoneal dialysis patients. In the peritoneal dialysis patients, paranoid ideation scores of female were higher than the scores of male. In the haemodialysis patients, hostility scores of male were higher than the scores of female. Conclusion: The results of this study indicate that hostility, phobic anxiety and psychosis are higher in peritoneal dialysis patients compared to haemodialysis patients. We suggest that dialysis patients especially on peritoneal dialysis and younger dialysis patients should be evaluated for mental symptoms and supported as needed.
Keywords: Anxiety; Depression; Haemodialysis; Mental symptoms; Peritoneal dialysis